Effects of physical activity on internalizing problems in adolescents with autism spectrum disorder: the chain mediating effects of sport friendship quality and social-emotional competence - Zhu, Yingbo; Li, Xiao; Du, Zhijuan (Frontiers in Psychology, 2025)
BackgroundAdolescents with autism spectrum disorder (ASD) often experience identity confusion, social difficulties, and internalizing symptoms such as anxiety and depression. Physical activity offers opportunities for peer interaction and teamwork, which may help alleviate negative emotions. This study aims to investigate the pathways through which physical activity influences internalizing problems in adolescents with ASD.MethodsA total of 436 adolescents with ASD were recruited using a combination of random and convenience sampling. Participants were assessed using the Physical Activity Rating Scale, the Strengths and Difficulties Questionnaire, the Social-emotional Competence Scale, and the Sport Friendship Quality Scale. Data were analyzed using SPSS 27.0 and Process 4.1 to examine the relationships among the four variables.Results(1) Physical activity predicted a decrease in internalizing problems, and positively predicted sport friendship quality and social–emotional competence. (2) Both sport friendship quality and social–emotional competence independently mediated the relationship between physical activity and internalizing problems. (3) Additionally, a sequential (chain) mediation effect was identified, whereby physical activity influenced internalizing problems through both mediators in sequence.ConclusionThese findings suggest that physical activity holds substantial potential for mitigating internalizing symptoms among adolescents with ASD and supports the development of sport-based friendships and social-emotional skills. Future research should consider age-specific characteristics and individual preferences for activity types to identify the most effective interventions for enhancing friendship, social–emotional competence, and mental health in this population.